REWARDING A LIVING KIDNEY DONOR: A COMPARISON BETWEEN SOUTH AFRICA, SINGAPORE AND IRAN - B Venter; M Slabbert (Obiter, 2021)
There are thousands of desperate people globally who need a kidney for transplantation. The number of people who require a kidney transplant continues to escalate faster than the number of kidneys available for a transplant. If South Africa wants to improve its current kidney-donation rate it should seek guidance from abroad. This article will compare South African transplant legislation with current legislation in Singapore and Iran. These two countries are of significance to the transplant debate as Singapore has recently legalized the reimbursement of costs of the organ donor while Iran goes a step further and pays the kidney donor. In conclusion it is argued that South Africa could learn from these two countries in order to try and address the shortage of transplantable organs locally.